O-017 Aneurysm treatment with web®: evaluation of the 21 system in a prospective, single-center series of 35 patients. (23rd July 2017) - Pierot, L; Soize, S; Gawlitza, M
Abstract : Neuroradiology, Hôpital Maison-Blanche, Reims, France. Purpose: WEB Flow disruption is an innovative endovascular treatment for wide-neck bifurcation aneurysms. Prospective multicenter GCP (Good Clinical Practice) studies conducted in Europe (WEBCAST, French Observatory, WEBCAST-2) and USA (WEB-IT) have shown the good safety and efficacy of the device in the treatment of wide-neck bifurcation aneurysms. This series is evaluating the performance of the 21 System. Methods: Patients with wide neck bifurcation aneurysms treated with WEB-21 were prospectively included in this single-center series conducted in Reims (France). Adverse events were reported and analyzed. Aneurysm occlusion was evaluated at the end of the procedure, 24 hour, 3 months, and 6 months using the 3 grade scale: complete occlusion, neck remnant, and aneurysm remnant. Results: A total of 35 patients (24 females, 68.6%) aged 32 to 78 years were included. Thirty-seven aneurysms were treated with WEB-21. Aneurysm location was middle cerebral artery in 18/37 aneurysms (48.6%), internal carotid artery in 7/37 (18.9%), anterior communicating artery in 6/37 (16.2%), and basilar artery in 6/37 (16.2%). Aneurysm size (transverse diameter) was between 2.5 and 6.9 mm. Neck size was greater than 4 mm in 16/37 aneurysms (43.2%). 35/37 aneurysms (94.6%) were treated with WEB SL and 2/37 (5.4%) with WEB SLS. Placement of the WEB device was feasible in 36/37 aneurysms (97.3%). In 1 patient, placement of the WEB was not possible due to the angle between the aneurysm and the parent artery. During catheterization of the aneurysm sac, perforation of the parent artery occurred leading to subarachnoid bleeding and death 4 days later (mortality: 1/37, 2.7%). No thromboembolic event or aneurysm rupture was observed during the treatment. There was no morbidity related to the procedure (0.0%). As of now, angiographic follow-up (3–12 months) was obtained in 31/37 aneurysms (83.8%). Anatomical results were complete aneurysm occlusion in 20/31 aneurysms (64.5%), neck remnant in 9/31 aneurysms (29.0%), and aneurysm remnant in 2/31 aneurysms (6.5%). Conclusion: This preliminary evaluation shows a good safety and efficacy of the WEB 21 system. Disclosures: L. Pierot: 2; C; Microvention/Sequent. S. Soize: None. M. Gawlitza: None.